Cost analysis of Occupational Health And Safety (K3) on the Road Preservation (Case Study : Road In Kendari City – Kendari City Boundary) - Usman, Febrianti; Sufrianto, Sufrianto; Hawa, Sitti; Isazarny Jassin, Andi Makkawaru (Universitas Sulawesi Tenggara, 2022)
The purpose of this study was to determine how much the application of K3 and to analyze the cost of K3 on the road preservation project within Kendari City - Kendari City boundary. The results showed that the level of use of PPE in road preservation work in the city of Kendari did not meet the standards for the level of use of PPE / included in the less category. This is because the average value of the level of use of PPE in road shoulder work, asphalt Ac-Wc and Talud is 60%. The cost required for the implementation of Occupational Safety and Health (K3) on the Road Preservation project. The required K3 cost based on the unit price of the regulation is IDR 266,645,950.00 or around 2.17%, while the cost based on field prices is IDR 257,953,950 or about 2.10%. The percentage of K3 costs at the regulation price is greater than the percentage of K3 costs at field prices with a difference of 0.07% or Rp. 8,692,000.00.